Incidence and survival of salivary gland cancer in children and young adults in Denmark: A nation-wide study for the period 1990–2015. (April 2021) - Jensen, Jakob Schmidt; Grønhøj, Christian; Garset-Zamani, Martin; Westergaard-Nielsen, Marie; Bjørndal, Kristine; Kiss, Katalin; Charabi, Birgitte; von Buchwald, Christian; Hjuler, Thomas
Abstract: Objectives: The aim of this study was to evaluate incidence and survival of children and young adults with salivary gland cancer (SGC) in Denmark during the period 1990–2015. Method: We included all patients aged 0–24 years registered with primary SGC in the Danish Cancer Registry, the Danish Pathology Data Bank, or the DAHANCA database during 1990–2015. Patients were divided in two age-groups: children (0–17 years) and young adults (18–24 years). Incidence rates, overall survival (OS), and recurrence free survival (RFS) was evaluated in relation to age-group, sex, tumor location, tumor histology, and T-, N-, and M-classification. Results: A total of 70 SGC patients between 0 and 24 years (67% female, n = 47) were included. Thirty-six were children at time of diagnosis, and 34 were young adults. The incidence was higher among young adults compared to children (0.29 vs. 0.11 per 100.000) and showed no significant change during the study period. There were no differences in the distribution of sex, tumor location, or tumor histology between children and young adults. The total 5 and 15-year survival rates were 97.1% and 91.7% for OS, and 97.1% and 83.1% for RFS. The survival rates showed no significant differences according to age-groups, sex, tumor location, or tumor histology. Patients diagnosed in stage T4 had significantly worse OS and RFS. Conclusion: The incidence of SGC among children and young adults in Denmark was low and stable in the period 1990–2015. The overall survival was very high, demonstrating the excellent prognosis for children and young adults with SGC.